The Queen's Daughters: White Prostitutes, British India and the Contagious Diseases Acts. Issue 1 (June 2017) - Jain, Sagaree
Within the larger subject of the regulation of prostitution under the British Empire in South Asia, this article examines the figure of the White Prostitute in brothels and lock hospitals in colonial India. The White Prostitute in colonial India was in every way segregated from her native counterparts: in medicine, in physical quarters and in popular conceptions of her mobility, agency and rationality. Despite their mistreatment and vulnerability in many sources, white prostitutes were understood as closer to the ideal of regulable, liberal subjecthood compared to Indian women working in the same conditions and ultimately demonstrated the dynamism of the conditions of prostitution in this time and place. Through examination of literature, advocacy and military records, this article contends that the figure of the White Prostitute fractured concepts of caste-based prostitution in India and was wielded by imperial feminists to attack British regulation of prostitution and sexual slavery in India for brown as well as white women.